Prevalence of post-traumatic stress disorder risk post-COVID-19 in 12 countries in Latin America: a cross-sectional survey - Mejia, Christian R. (2023)
Introduction: Latin America was the region most affected by COVID-19 in the second quarter of 2020, and consequently, the impact on mental health requires evaluation. The aim of this study was to assess the risk of post-traumatic stress disorder (PTSD) caused by bereavement due to COVID-19 in 12 countries in Latin America. Methods: The current study was an analytical cross-sectional study. Validated tests were applied for PTSD, depression, anxiety, and stress (DASS-21), questions about the respondent’s condition or their environment, and demographic questions, as well as the length of the mourning period of suffering. Results: The outcomes demonstrated that the PTSD risk increased for women (p < 0.001), when a friend or acquaintance had COVID-19 (p = 0.002), when a close relative died from COVID-19 (p = 0.010), having severe depression (p <0.001), severe anxiety (p <0.001), severe stress (p <0.001), residing in Chile (p <0.001), Paraguay (p <0.001), Bolivia (p <0.001), Costa Rica (p <0.001) or El Salvador (p = 0.005). On the other hand, there was less risk of PTSD at an older age (p <0.001) or if respondents had a sentimental partner (p = 0.025). In the case of severe PTSD, there was a greater gender risk for women (p <0.001), a close relative dying from COVID-19 (p = 0.017), having severe depression (p <0.001), severe anxiety (p <0.001), severe stress (p <0.001), residing in Chile (p <0.001), Paraguay (p <0.001), Bolivia (p <0.001) and Costa Rica (p = 0.002). It was also observed that there was less risk of severe PTSD at an older age demographic (p <0.001). Discussion: It can be concluded that the percentages of PTSD are high in its clinical presentation as severe, especially among Latin American women.